A7.13 Distinct expression of IL-36α, β, γ and their antagonists IL-36RA and IL-38 in psoriasis, rheumatoid arthritis (RA) and crohn's disease (CD). (24th February 2016) - Boutet, MA; Bart, G; Gahier, M; Amiaud, J; Brulin, B; Charrier, C; Morel, F; Lecron, J-C; Rolli-Derkinderen, M; Boureille, A; Vigne, S; Gabay, C; et al.
Abstract : Background and objectives: The IL-36 family of cytokines comprises three agonists: IL-36α, IL-36β and IL-36γ, an antagonist: IL-36Ra, and IL-38: another potential IL-36 inhibitor. IL-36 agonists are highly expressed in skin and are involved in the pathogenesis of psoriasis, while antagonists limit uncontrolled inflammation. The expression and role of IL-36 cytokines in other chronic inflammatory diseases is currently debated. In this study, we compared the expression profile of IL-36 cytokines in psoriasis, RA and CD. Materials and methods: Skin, joint and colon inflammation was induced in mice. Skin, synovial and colonic biopsies from patients respectively with psoriasis, RA or CD were collected. Synovial fluids from patients with RA were also collected. These samples were analysed for cytokines expression by RT-qPCR, ELISA, immunohistochemistry and confocal microscopy. The cell sources of IL-36 cytokines were confirmed in cell cultures after stimulation with inflammatory cytokines and TLR agonists by RT-qPCR. Results: During imiquimod-induced mouse skin inflammation and in human psoriasis, expression of IL-36α, γ and IL-36Ra, but not IL-36β and IL-38, was induced and correlated with Th17 cytokines (IL-17A, IL-22…). In mice with collagen-induced arthritis and in the synovium of patients with RA, IL-36α, β, γ, IL-36Ra and IL-38 were all elevated and correlated with myeloid cytokines such as CCL3, CCL4 and MCSF, but not with Th17 cytokines. In mice with dextran sulfate sodium-induced colitis and in patients with CD, only IL-36α, γ and IL-38 were induced at a relatively low level. Only a minor subgroup of patients with RA (17–29%) or CD (25%) had an elevated IL-36 agonists/antagonists ratio, versus 93% of patients with psoriasis. By IHC and in cell cultures, the different IL-36 cytokines were produced at different levels by human keratinocytes, CD68 + inflammatory macrophages, dendritic/Langerhans cells, and CD79α + plasmocytes. Conclusion: Expression of the different IL-36 cytokines is differently regulated and their cell sources are distinct. This helps to explain the different expression profiles observed in three chronic inflammatory diseases and why only a minor subgroup of RA and CD patients have an elevated IL-36 agonists/antagonists ratio. Additional studies are necessary to better identify these patients and to investigate whether they would benefit from IL-36 neutralisation.